Adhesion and wear behavior of nanostructured titanium oxide thin films - Hasan, M.M.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan; Saidur, Rahman (International Journal of Mechanical and Materials Engineering, 2010)
This study aims to investigate structural, mechanical and tribological properties of titanium oxide films deposited on glass substrates by radio frequency (RF) magnetron sputtering. All the as-grown titania films possess the anatase structure having a grain size of about 44 nm irrespective of the variation of substrate temperatures. AFM images show a nodular morphology with an increase of surface roughness. From micro-scratch tests, the optical micrographs of the scratch tracks show that the complete delamination of TiO 2 films deposited at higher temperatures appear at a higher value of adhesion critical loads. The highest adhesion critical load between titanium oxide films and glass was found to be 2.24 N for the film prepared at 300 Â°C. It represents an enhanced adhesion strength for films deposited at higher temperatures. Scratch hardness was also found to increase from 5.5 to 8.4 GPa with increasing substrate temperature. From micro-wear test, it is found that the wear resistance of TiO 2 films deposited at higher substrate temperatures exhibits higher wear resistance.